Myphotoprint application – Enabling two businesses into one as integrated mobile system, web application and management system - Zai Zani, Muhammad Syahmi; Mohamed Husain, Muhammad Faris Husaini; Rajie, Mohd Azam; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The purpose of the paper was to instigate or proposing a proper solution that were faced by the two main key partners in the business model canvas which were Fariz Huzaini Photography and Photobook Worldwide as the main idea was to join both business using new combined business model. There will be various aspects that will be analysed before a new solution can be developed including studying competitors business model canvas (BMC), environmental map (EM) and value proposition canvas (VPC), interviewing related people with the business (management, customers and etc) and also provide various alternatives for the new BMC, EM as well as VPC. The pains such as long service time and customers’ limited budget have become one of the main focus to be solve. A fast services and cheaper alternatives needed in order to enhance the customers’ experience. The researcher used the four lenses of innovation methodology to design the solution for these problems. Myphotoprint Application has been proposed with the hopes that this application will deliver the services in time, reduce the cost of service. The summary is made to conclude the aspects discussed in the paper.